Zai improves nutrient and water productivity in the Ethiopian highlands - Amede, Tilahun; Menza, M.; Awulachew, Seleshi Bekele (Cambridge University Press, 2011)
In the East African highlands, crop yields tend to increase with proximity of the farm plots to homesteads. Farmers identified soil erosion as the most detrimental cause of low crop yield in the outfields followed by soil compaction due to livestock trampling. The main objective of this study was to determine whether zai pits (i.e. small water harvesting pits) developed for dryland regions of the Sahel could increase crop yield and water productivity of degraded outfields in high rainfall areas, where mean annual rainfall exceeds 1300mmbut soil water infiltration is reduced by slope, low soil organic matter and hardpans. The pits were enlarged to resist strong runoff flows. The research was conducted over three years from 2004 to 2006. Potatoes and beans were used as test crops. Overall, compared to control plots, the zai pits, in combination with nitrogen (N) inputs, increased potato yields from 500% to 2000% ( p ≤ 0.001). The pits contributed more to increased crop yield than N inputs. Similarly, bean yields from the zai pits were up to 250% higher. Crop water productivity was 300–700% higher with zai pits than with control plots. The income of farmers who used zai pits was up to 20-fold higher than the labour costs required to prepare them. Contrary to conventional wisdom, this study reveals that the major constraint of the outfields is not nutrient deficiency per se rather low soil water holding capacity, which hinders crop growth and efficient utilization of available nutrients.